METHODS OF TEACHING MATHEMATICS IN PRIMARY CLASSES - Imamova Nasiba Xurramovna (Zeta Repository, 2023)
The article provides information about the methods of teaching mathematics, the specific features of the methods. Induction, deduction, analogy methods are given in detail.